Clustering Village Zones Based On Nutritional Status of Toddlers Using The K-Medoids Method - Amelia, Ulva; Yunizar, Zara; Rosnita, Lidya (Akademi Komunitas Negeri Aceh Barat, 2025)
AbstractIn order to improve the effectiveness of nutrition intervention planning in the operational area of the Kuta Blang Health Center, this study aims to develop a village zoning model based on the nutritional status of toddlers using the K-Medoids algorithm. The primary data includes the distribution of nutritional statuses (good, overnutrition, undernutrition, severe malnutrition, obesity) from 41 villages collected during the January–December 2023 period. Data were normalized and processed using a web-based system developed in PHP and MySQL. The clustering process resulted in five zones: Green (optimal nutrition), Yellow (within acceptable limits), Orange (requires monitoring), Red (worst condition), and Purple (critical challenges). Field validation showed strong alignment between clustering results and real conditions. This study concludes that the K-Medoids method can accurately group villages based on nutrition data and produce a practical zoning map. The resulting zones allow for more efficient resource allocation and targeted intervention, especially in Red and Purple zones. Future improvements may include incorporating socioeconomic and healthcare access variables for more comprehensive analysis. AbstrakDalam rangka meningkatkan efektivitas perencanaan intervensi gizi di wilayah kerja Puskesmas Kuta Blang, penelitian ini bertujuan untuk mengembangkan model zonasi desa berdasarkan status gizi balita menggunakan algoritma K-Medoids. Data primer meliputi distribusi status gizi balita (gizi baik, gizi lebih, gizi kurang, gizi buruk, obesitas) dari 41 desa yang dikumpulkan selama periode Januari–Desember 2023. Data tersebut dinormalisasi dan diolah dalam sistem berbasis web menggunakan bahasa pemrograman PHP dan database MySQL. Proses klasterisasi menghasilkan lima zona: Hijau (gizi optimal), Kuning (masih dalam batas wajar), Oranye (perlu pemantauan), Merah (terburuk), dan Ungu (tantangan signifikan). Validasi lapangan menunjukkan kesesuaian tinggi antara hasil klasterisasi dan kondisi nyata. Penelitian ini menyimpulkan bahwa metode K-Medoids mampu mengelompokkan desa secara akurat berdasarkan data gizi dan menghasilkan peta zonasi yang aplikatif. Zona yang dihasilkan memungkinkan alokasi sumber daya dan intervensi yang lebih terarah, khususnya pada zona Merah dan Ungu. Perbaikan di masa depan dapat mencakup integrasi variabel sosial ekonomi dan akses layanan kesehatan untuk analisis yang lebih komprehensif